2018
DOI: 10.2166/ws.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

The application of ensemble precipitation forecasts to reservoir operation

Abstract: Although inflow forecasts are useful information that can be used for improving reservoir operation efficiency, uncertainty is still a challenge for getting sound operation results. Ensemble precipitation forecasts can take uncertainties under consideration, so they have been a research topic for improving reservoir operations. In this paper, a rainfall–runoff model, combined of a multiple linear regression model (for non-flood seasons) and the Xinanjiang model (for flood seasons), for inflow forecasts and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The BayesGLM model has never been used for flood susceptibility mapping or any other hydrological modeling up until now. But the popularity of boosting in the advancement of ensemble machine learning methods for hydrological modeling including the flood prediction has been fast-growing due to their accuracy (Antonetti et al, 2019;Berkhahn et al, 2019;Gomez et al, 2019;Lee et al, 2017;Peng et al, 2019;Tian et al, 2019).…”
Section: Model Evaluation Resultsmentioning
confidence: 99%
“…The BayesGLM model has never been used for flood susceptibility mapping or any other hydrological modeling up until now. But the popularity of boosting in the advancement of ensemble machine learning methods for hydrological modeling including the flood prediction has been fast-growing due to their accuracy (Antonetti et al, 2019;Berkhahn et al, 2019;Gomez et al, 2019;Lee et al, 2017;Peng et al, 2019;Tian et al, 2019).…”
Section: Model Evaluation Resultsmentioning
confidence: 99%
“…The combined effects of price and streamflow forecasts on water resource allocation are worth investigating in future studies. Our study also suffers from the drawback that instead of using the short-term weather forecasts from the Global Forecast System (GFS) or European Centre for Medium-Range Weather Forecasts (ECMWF) model (Choong and El-Shafie, 2015;Schwanenberg et al, 2015;Peng et al, 2018;Ahmad and Hossain, 2019;, we used the observed weather conditions as alternatives, which may result in an overestimation in forecast quality. However, forecast uncertainty and error generally grow with lead time.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The combined effects of price and streamflow forecasts on water resource allocation are worth investigating in future studies. Another limitation is that instead of the short-term weather forecasts from the Global Forecast System (GFS) or European Centre for Medium-Range Weather Forecasts (ECMWF) model (Choong and El-Shafie, 2015;Schwanenberg et al, 2015;Peng et al, 2018;Ahmad and Hossain, 2019;, we used the observed weather conditions as alternatives, which may result in an overestimation in forecast quality. However, forecast uncertainty and error that generally grow up with lead time.…”
Section: Figure 15 Is Herementioning
confidence: 99%